Causal association of type 2 diabetes with central retinal artery occlusion: a Mendelian randomization study - Liu, Tong; Lu, Qingli; Liu, Zhongzhong; Lin, Xuemei; Peng, Linna; Lu, Xiping; Guo, Weiyan; Liu, Pei; Zhang, Na; Wu, Songdi (Frontiers in Endocrinology, 2024)
Background: Central retinal artery occlusion (CRAO) is a medical condition characterized by sudden blockage of the central retinal artery, which leads to a significant and often irreversible loss of vision. Observational studies have indicated that diabetes mellitus is a risk factor for CRAO; however, there is no research on the causal relationship between diabetes mellitus, particularly type 2 diabetes, and CRAO. This study aimed to perform Mendelian randomization (MR) analysis to clarify the causal relationship between type 2 diabetes and CRAO.Methods: Genetic variants associated with type 2 diabetes were selected from two different datasets. A recent genome-wide association study of CRAO conducted using the FinnGen database was used as the outcome data. A two-sample MR was performed to evaluate the causal relationship between type 2 diabetes and CRAO. Inverse variance weighting was the primary method, and MR-Egger, maximum likelihood, and median weighting were used as complementary methods. A multivariate MR (MVMR) analysis was performed to further evaluate the robustness of the results. Cochran's Q test, MR-Egger intercept test, and MR-PRESSO global test were used for the sensitivity analyses.Results: Genetically predicted type 2 diabetes was causally associated with CRAO(odds ratio [OR] =2.108, 95% confidence interval [CI]: 1.221-3.638, P=7.423×10 -3 ), which was consistent with the results from the validation dataset (OR=1.398, 95%CI: 1.015-1.925, P=0.040). The MVMR analysis suggested that type 2 diabetes may be an independent risk factor for CRAO (adjusted OR=1.696; 95%CI=1.150-2.500; P=7.655×10 -3 ), which was assumed by the validation dataset (adjusted OR=1.356; 95%CI=1.015-1.812; P=0.039).Our results show that genetically predicted type 2 diabetes may be causally associated with CRAO in European populations. This suggests that preventing and controlling type 2 diabetes may reduce the risk of CRAO.